The determination of the perceived stress levels and health‐protective behaviors of nursing students during the COVID‐19 pandemic - Ersin, Fatma (Perspect Psychiatr Care, 2020)
PURPOSE: The study was carried out to determine the perceived stress levels and health‐protective behaviors of nursing students during the COVID‐19 pandemic. DESIGN AND METHODS: This study used a descriptive design. The sample consisted of a total of 372 students. FINDINGS: The examination of the protective measures adopted by the students against COVID‐19 indicated that the mean perceived stress subscale scores of the students who did not use a mask and disposable wipes when coughing/sneezing were statistically significantly higher (p < .005). PRACTICE IMPLICATIONS: The stress levels of students should be determined at certain intervals, and interventional studies on coping methods that will reduce stress levels should be planned.